SUSTAINABLE DEVELOPMENT AND HEALTH: A REGIONAL ASSESSMENT ON TÜRKİYE (Third Sector Social Economic Review, 2023)
The concept of “sustainable development” which has found widespread use in 1987 after the publication of “Brundtland” also known as “Our Common Future” Report and defined as “development that meets the needs of the present without compromising the ability of future generations to meet their own needs”, contains economic, social and environmental dimensions. Health is located in the intersection cluster of economic, environmental and social dimensions, which should be given simultaneous importance in order to achieve sustainable development. In addition to the fact that the concept of health is in the intersection cluster of these indicators, the goals of “reducing child mortality”, “improving maternal health” and “combating HIV/AIDS, malaria and other diseases” in “The Millennium Development Goals” and the goal of “ensuring healthy lives and promoting well-being for all at all ages” in “The Sustainable Development Goals” indicate the health-related aspect of sustainable development. From this point of view, this study aims to reveal the health-related aspect of sustainable development by evaluating the situations at the regional level in Türkiye of the indicators which are determined according to the goal of “ensuring healthy lives and promoting well-being for all at all ages” in “The Sustainable Development Goals” with a comparative descriptive analysis method.  The results of this study, which examines the data of the 12 regions at Level 1 of “The Nomenclature of Territorial Units for Statistics (NUTS)” in Türkiye for the years 2015 and 2019, reveal that there are regional differences in terms of the health-related aspect of sustainable development in Türkiye. Accordingly, in the context of sustainable development in Türkiye, ""TR5 West Anatolia"" and ""TR3 Aegean"" regions are the most advantageous regions in terms of health, while ""TRB Middle East Anatolia"" region is the most disadvantaged region. In addition, the number of doctors and dentists per 100,000 people is the indicator with the highest number of disadvantaged regions compared to Türkiye in general.
Keywords: Sustainability; Sustainable Development; Environment; Health; Regional Data